The effect of applying design thinking models on students of Packaging design to develop skills of creative thinking - Mysara Atef Al Moteey (Journal of Architecture, Art & Humanistic Science, 2021)
There is no doubt that students of practical and technical specializations (of an innovative and creative nature) suffer a lot in order to achieve good levels of innovation and modernity, especially when they are exposed to the problems of applied design, and this research indicates the need to apply an educational curriculum that improves their creativity and develops their innovative ideas through The acquisition of design thinking skills, in particular for students in packaging design, and this approach to thinking is an alternative to the traditional curricula and teaching methods followed in technical and design specializations in general and in the specialty of packaging design in particular, as the research highlights us as specialists in teaching design and teaching the fields of applied arts of interest Using innovative techniques and methodologies that enhance our students ’creative and innovative thinking skills, and this was the purpose of this study.Design Thinking Model is a method or method of teaching that has been applied to students of the Design Department, specifically within the packaging design course at Al-Zahra College for Girls in Muscat Governorate, Sultanate of Oman, and it follows in the college’s system of study the use of a “project-based learning” approach for all design materials and courses. The design thinking model has been implemented through many semesters between the academic year 2016 and the academic year 2020. Many students were honored after winning many international and local competitions and competitions through their projects produced in those courses in which they were taught the design thinking methodology .This study provides evidence that the design thinking methodology is a successful educational strategy that develops the creative thinking activity and enhances the innovative skills of students, produces unique and distinctive design solutions, receives rapid spread within the field of real work and provides great opportunities of experience for packaging design students in particular.